Analysis of agreement between specialists for the evaluation of radiological findings of necrotizing enterocolitis - Erica Cristina Scarpa; João C. Lyra; Pedro L.T. de A. Lourenção; Andréa S. Hachem; Geraldo H.S. da Silva; Glauce R.F. Giacóia; Erika V.P. Ortolan; Camila de Paula Silva; Guilherme L. da Silveira; Maria R. Bentlin (Jornal de Pediatria, 2025)
Objective: The analysis of abdominal radiography is essential for the diagnosis and management of necrotizing enterocolitis (NEC) in newborns (NB). Studies, however, show a lack of agreement among physicians in the interpretation of images. This study aims to evaluate the agreement in the radiological interpretation of the NEC between examiners from different specialties (interexaminer analysis) and between the same examiner at different times (intraexaminer analysis). Methods: Cross-sectional study for concordance analysis using plain radiographs of the abdomen of NB with suspected or confirmed NEC. The study included two neonatologists (Neo), two surgeons (SU), and two radiologists (RD). The participants filled out a form with questions about the radiographic findings; regarding the presence of intestinal loop distension, the specialists answered subjectively (yes or no) and objectively (calculation of the ratio between loop diameter and lumbar vertebrae measurements). Kappa coefficients were calculated for agreement analysis. Results: A total of 90 radiological images were analyzed. For the interexaminer evaluation, the agreement was low (kappa<0.4) in 30 % of the answers (Neo versus SU), 38 % (Neo versus RD), and 46 % (SU versus RD). In the intraexaminer evaluation, the neonatologist and the surgeon presented substantial or almost perfect agreement in 92 % of the answers, and the radiologist in 77 %. In the evaluation of intestinal loop distention, the greatest agreement between the specialties occurred when done objectively. Conclusion: The results confirmed the low intra- and interexaminer agreement in the radiological analysis of the NEC, reinforcing the importance of standardizing the methods of radiological interpretation of the disease.